UJI DAYA TERIMA DAN NILAI GIZI BISKUIT YANG DIMODIFIKASI DENGAN TEPUNG KACANG MERAH - PETTI SITI FATIMAH; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Red bean is one of the types of nuts that are potentially to be developed in a variety of industrial products food. Red Bean have a nutritional quality is not inferior to other types of nuts, but its utility becomes food hawker is still limited. Red bean flour can be processed to various food product that can give his nutrient contributing such as food hawker a schoolchild. One such product is the biscuit. The purpose of this research is to know the nutrient content and acceptability from a biscuit with addition of red bean flour. This research is a research experiment, that is the manufacture of biscuits with the addition of red bean flour by 10%, 17.5% and 25%. Panelists in this study are elementary school students of SDN 067097, as many as sixty people. Acceptance of test data obtained were analyzed by descriptive and nutrient value of protein and fiber is determined using the Kjeldhal Method and Gravimetry Method in the test in Research Agency and Industrial Standardization Laboratory Medan. The result showed that the acceptability of students elementary school against granting biscuit by the addition of flour red beans who favored is biscuit by the addition of 10 % The addition of flour red beans in making biscuits give increased amount of protein and fibers in biscuit The addition of flour red beans in making biscuits with wide variations give the influence of different real the assessment test acceptability both in terms of texture and flavor and the resulting nutritional biscuits Then it is advisable to socialization of information that can be made and received biscuits from red bean flour is primarily used as a additional food school children. Further research needs to be done to see the micro-nutrient content contained on red bean flour Keywords: Biscuits, Red Beans Flour, Acceptability Test, Elementary School